Effectiveness of Career Construction Theory (CCT) in Reducing College Students Career Anxiety: Systematic Literature Review - Sari, Arlina; Sugiharto, Dwi Yuwono Puji; Sunawan, Sunawan (Grief and Trauma, 2023)
Entering the transition period from college to the world of work presents many challenges and uncertainties, causing intense anxiety for students. This condition causes students who are at the tertiary stage of development to experience a decline in mental health and experience a series of career anxieties. This study aims to determine the effectiveness of career construction theory (CCT) intervention in reducing career anxiety in students in higher education. This research uses a systematic review of the Eric Journal and Science Direct databases. The search used Career Construction Theory (CCT), Career Adaptability, Career Anxiety, and College Students. From the search results, 320 articles were found and filtered using the PRISMA method until 6 articles matched the discussion and met the inclusion criteria. The research results show that career construction theory (CCT) intervention significantly reduces career anxiety in students. Therefore, career construction theory (CCT) intervention is needed to assist career development in higher education and help deal with career anxiety problems in students. Thus, career construction theory (CCT) intervention is valuable in assisting students to prepare themselves to achieve career success as expected.